PENGARUH LAYANAN INFORMASI BERBASIS CAREER MAPPING TERHADAP KEMAMPUAN MEMILIH JURUSAN PERGURUAN TINGGI PADA SISWA KELAS XI SMA NEGERI 1 STABAT - Dian Putri Pratiwi; Asih Menanti (STKIP Subang, 2026)
This study aims to determine the influence of career mapping-based information services on the ability to choose a college major in students of SMA Negeri 1 Stabat. The research method used in this study is quantitative research with a quasi-experimental approach. The data collection tool used was a Likert scale questionnaire about the ability to choose a college major. The research subjects consisted of 35 students of grade XI. Data analysis was carried out quantitatively using a paired sample t-test to see the difference in the ability to choose a major before and after receiving career mapping-based information services. The results showed that the normality test value obtained a Sig. value >0.05 with a pretest value of 0.077 and a posttest of 0.083, and in the linearity test a coefficient of 0.699> 0.05 was obtained which means that the data was normally and linearly distributed. In the t-test, a Sig. value <0.05 was obtained, namely (0.01) and from the pretest and posttest tables, a t-count of 32.768> t-table 2.032 was obtained which proved that the hypothesis was accepted. This also proves that there is an influence of career mapping-based information services on the ability to choose a college major.